(untitled) - Tillery, Bill W. (New York, NY, 2007)
"Physical Science, Seventh Edition", is a straightforward, easy-to-read, but substantial introduction to the fundamental behavior of matter and energy. It is intended to serve the needs of non-science majors who are required to complete one or more physical science courses. It offers exceptional, straight-forward writing, complimented with useful pedagogical tools. Tillery introduces basic concepts and key ideas while providing opportunities for students to learn reasoning skills and a new way of thinking about their environment. No prior work in science is assumed. The text offers students complete coverage of the physical sciences with a level of explanation and detail appropriate for all students. The sequence of chapters in "Physical Science" is flexible, and the instructor can determine topic sequence and depth of coverage as needed. The materials are also designed to support a conceptual approach, or a combined conceptual and problem-solving approach.
Keywords: Physical sciences,Khoa học vật lý